DEVELOPMENT OF INTRAUTERINE INFECTION CAUSED BY HERPESVIRIDAE: A ROLE OF C D14, TLR2, TLR6 ALLELIC POLYMORPHISM - M. M. Mironenko; T. I. Dolgikh (Медицинская иммунология, 2014)
We present a clinical case of a viral intrauterine infection in an infant with certain combination of CD14, TLR2, TLR6 gene polymorphisms. A possible mechanism is proposed for development of fatal outcome in such prenatal infections.